Out-of-equilibrium quantum magnetism and thermalization in a spin-3 many-body dipolar lattice system - S. Lepoutre (Nature Portfolio, 2019)
Isolated many-body quantum systems do not thermalize with an external environment but in most cases the internal dynamics leads to the emergence of an effective thermal equilibrium for local degrees of freedom. Here the authors study this behaviour with a realization of a long-range spin model.